Sociální péče v meziválečném Československu - Vohradníková, Lucie (Univerzita Pardubice, 2009)
The paper focuses on the understanding of the term "Social Care" in the years 1918 - 1938. Futher, it engages in the organization of social care in interwar Czechoslovakia. It describes the circumstances that influenced its development and function considerably, and refers to some of its strengths and weaknesses.
Keywords: social care; first republic; interwar period; public social care; voluntary social care